The Moderating Effect Of Social Class Between Halal Cosmetics Consumption Value And Purchase Intention Among Malaysian Consumers - Liew, Wan Shean (2024)
Despite the potentially significant contributions of Halal cosmetics to unsustainable issues, they are not the preferred choice among Malaysian consumers. Therefore, this study uses the consumption value theory to understand consumer purchase intention for Halal cosmetics. Data was collected from 185 Muslim and non- Muslim respondents through an online survey and analyzed using PLS-SEM. The study provides a novel perspective on Halal cosmetics consumption value, highlighting associated context-specific attributes in functional, social, emotional, epistemic, and conditional value. The findings indicate that emotional value strongly influences consumers’ purchase intention for Halal cosmetics, followed by epistemic, conditional, and functional value, particularly in sustainability and safety attributes. Furthermore, moderation analysis reveals that the positive relationship between conditional value and purchase intention for Halal cosmetics is strengthened among consumers with a higher social class. This study provides valuable insights into consumers’ purchase intentions concerning context-specific consumption values for Halal cosmetics.